Biodiversity and Carbon Storage Potential in the Lambosir Hill Area, Mount Ciremai National Park, Kuningan Regency, West Java Province - Alvin Amanda Simamora; Bakti Wisnu Widjajani; Rossyda Priyadarshini (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
The potential for biodiversity, including a variety of tree, shrub, and bush species, is particularly pronounced in ecosystems characterized by high biodiversity, which influences the soil's capacity to retain water—the greater the species diversity within an ecosystem, its ability to sequester CO2 increases. Lambosir Hill is one of the hills located within the protected forest area of Mount Ciremai National Park (TNGC). This study aimed to assess the level of plant vegetation diversity on Lambosir Hill and examine the relationship between biodiversity and carbon stocks. This study was conducted in Lambosir Hill, Mount Ciremai National Park in Kuningan Province, West Java. This study began in November 2022 and ended in March 2023. Activities related to data processing were carried out at the Land Resources Laboratory, Faculty of Agriculture, National Development University “Veteran” East Java. The study results showed low diversity at the shrub level and moderate at the tree level. The highest carbon stock was found in Sonokeling and the weakest in Hamerang. The land use type, slope, and vegetation composition influence these values’ differences. These results show the importance of permanent vegetation in supporting carbon stocks and ecosystem stability. It is recommended that woody tree vegetation such as Sonokeling be preserved to maintain the sustainability of carbon reserves in this conservation area.